A Case-Control Study of the Role of Human Papillomavirus in Oesophageal Squamous Cell Carcinoma in Australia. (28th April 2014) - Liyanage, Surabhi S.; Segelov, Eva; Malik, Aisha; Garland, Suzanne M.; Tabrizi, Sepehr N.; Cummins, Eleanor; Seale, Holly; Rahman, Bayzidur; Moa, Aye; Barbour, Andrew P.; Crowe, Philip J.; MacIntyre, C. Raina
Abstract : Objective . We investigate the prevalence of human papillomavirus (HPV) in oesophageal squamous cell carcinoma (OSCC) tissues compared to oesophageal tissue from healthy controls, in an Australian cohort. Methods . We conducted a hospital-based case-control study of 99 patients with OSCC and 100 healthy controls to examine the presence of HPV DNA. Paraffin tissues were tested using the PapType high-risk HPV detection and genotyping kit and with INNO-LiPA HPV Genotyping Extra. The biopsy samples were tested for HPV using a PCR-ELISA method based on the L1 consensus primer set PGMY09-PGMY11. Results . HPV DNA of the oncogenic genotype 16 was detected in 1/99 case specimens, a rate of 1010 per 100, 000 (95% CI: 30–5500). All control specimens were negative for HPV. Significantly higher rates of smoking, other aerodigestive cancers, and mortality were seen among cases than controls. A pooled analysis of this study and the only other Australian case-control study found that 9/321 cases and 0/155 controls were positive for HPV. The pooled odds ratio for HPV being a risk factor for OSCC was 9.35 (95% CI: 0.47–190.33). Conclusion . Our results suggest that in this multifactorial cancer HPV may be an additional risk factor; although a larger, better powered study is needed.